The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae) - Paul, Jimmy; Sankaran, Pradeep M.; Joseph, Mathew M.; Sebastian, Pothalil A. (Zootaxa, 2016)
The orb-weaving spider genus Plebs Joseph & Framenau, 2012 currently has only two representatives in India: Plebs himalayaensis (Tikader, 1975) from the Himalayas and Plebs mitratus (Simon, 1895) from the Nilgiris and Anamudi Shola National Park (World Spider Catalog 2016), both are found in high altitude mountainous habitats (Joseph & Framenau 2012). Both species were known only from females (World Spider Catalog 2016), although Sherriffs (1918, 1919) provided a description of an immature male of P. mitratus. In the present paper, we provide the first description of the adult male of P. mitratus, together with the detailed redescription of its female demonstrating considerable intraspecific variation.